Water and Alkali Leaching for Simultaneous Iron and Alumina Separation from Hydrogen-Reduced Bauxite Residue-Calcite Pellets - Manish Kumar Kar; Casper van der Eijk; Jafar Safarian (Materials Proceedings)
Iron and alumina can be separated from bauxite residue and calcite self-hardened reduced pellets through simultaneous magnetic separation and alkali leaching. Bauxite residue and calcite self-hardened pellets were reduced non-isothermally by hydrogen gas to obtain metallic iron. Thereafter, the fine grounded reduced pellet powder was leached with a simultaneous magnetic stirrer, while two different leaching processes were applied. In a magnetic stirring alkali-leaching process, the simultaneous leaching and magnetic separation by Na2CO3 solution was carried out. In another process, the reduced pellets were leached into water with gradual magnetic separation followed by the addition of Na2CO3 solution. X-ray diffraction, scanning electron microscopy, X-ray fluorescence, and inductively coupled plasma mass spectroscopy were used to conduct phase analysis, microstructural analysis, compositional analysis, and elemental analysis of the leaching solutions, respectively. It was found that, there was an increase in iron in the magnetic fraction as compared to a nonmagnetic fraction in both the leaching processes; however, the iron recovery is more noticeable in the magnetic alkali leaching process. The recovery of alumina depends upon the amount of mayenite formation during reduction. The greater the amount of mayenite and the lower the amount of gehlenite, the greater the alumina recovery will be. The simultaneous alkali leaching and magnetic separation lead to greater unlocking of the reduced matrix and to greater iron and alumina recovery compared to magnetic water leaching followed by alkaline leaching.